The Effect of Independent Commissioners, Company Size, Audit Committee on Tax Avoidance (Empirical Study on Mining Sector Companies Listed on the Indonesia Stock Exchange in 2019 - 2023) - Desmalia Putri; Safira Safira (Proceeding International Annual Conference Economics, Management, Business, and Accounting, 2025)
This study aims to examine the influence of Independent Commissioners, Company Size, and Audit Committee on tax avoidance. The presentation of this research is carried out by analyzing data from the annual financial reports of mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. The sample in this study consists of 24 companies with complete data available for five periods, resulting in 120 data points using the purposive sampling method. The tests used include descriptive statistical analysis, classical assumption tests, model suitability tests, and hypothesis testing. Data processing was conducted using the Statistical Product and Service Solutions (SPSS) version 25 application. The dependent variable in this study is Tax Avoidance, while the independent variables are the influence of Independent Commissioners, Company Size, and Audit Committee. The results of the study indicate that Independent Commissioners and Audit Committee have no significant effect on tax avoidance, whereas Company Size has a significant effect on tax avoidance.